Spillover Effects of Maternal Anemia on Neonatal Outcomes and Cord-Blood Ferritin: A Cross-Sectional Study at Ulin General Hospital, Banjarmasin - Andayani, Pudji; Kasab, Julia; Anggriana, Monica; Halim, Pricilia Gunawan; Yunanto, Ari (Nurture, 2025)
Maternal anemia is a widespread condition whose downstream effects are a spillover impact on fetal development and iron reserves. Understanding its impact on neonatal outcomes and cord-blood ferritin in Indonesian settings is critical for improving perinatal care. To evaluate how maternal anemia affects neonatal anthropometry, outcomes, and cord-blood ferritin. We conducted a cross-sectional study (June–October 2023) at Ulin General Hospital. Sixty mother–newborn pairs were enrolled via convenience sampling. Mothers were stratified by third-trimester hemoglobin (<11 g/dL vs. ≥11 g/dL). Data normality was assessed with Shapiro–Wilk; continuous variables compared by independent t-test or Mann–Whitney U; categorical by χ² or Fisher’s exact; correlations by Spearman’s rank (p < 0.05). Among 60 mother–newborn pairs, demographic and clinical features were comparable except for maternal education: primary schooling was more frequent in anemic mothers (73.3% vs. 46.7%, χ²=4.44; p=0.035). Newborns of anemic mothers had significantly lower median birth weight (2655 g [IQR 2459–2958] vs. 3103 g [IQR 2500–3300]; p=0.028) and length (47 cm [IQR 45.8–48] vs. 48 cm [IQR 46.4–49]; p=0.027). Cord-blood ferritin was markedly reduced in the anemia group (187 ng/mL [IQR 150–220] vs. 250 ng/mL [IQR 200–300]; p<0.001). Rates of preterm birth, survival to discharge, and median hospital stay did not differ between groups. Maternal hemoglobin correlated positively with neonatal ferritin (rₛ=0.253; p=0.050). Maternal anemia exerts spillover effects on neonatal growth and iron stores at birth, manifesting as lower birth weight, length, and cord-blood ferritin.